Respuesta :

Answer: [tex]\Large\boxed{14}[/tex]

Step-by-step explanation:

Given expression

[tex]x^2-2(x-y)[/tex]

Given information

[tex]x=-2[/tex]

[tex]y=3[/tex]

Substitute values into the expression

[tex]=(-2)^2-2((-2)-(3))[/tex]

Simplify the values in the parenthesis

[tex]=(-2)^2-2(-2-3)[/tex]

[tex]=(-2)^2-2(-5)[/tex]

Simplify the exponents

[tex]=4-2(-5)[/tex]

Simplify by multiplication

[tex]=4-(-10)[/tex]

[tex]=4+10[/tex]

Simplify by addition

[tex]=\Large\boxed{14}[/tex]

Hope this helps!! :)

Please let me know if you have any questions